Key Performance Indicator (KPI) Dashboard for buyers and shopping cart tracker in KL PSC - Sunderam, Danurshantini (IRC, 2019)
A performance dashboard enables managers to measure, monitor and manage the firm's performance more effectively. The research describes on the development of dashboards to show buyers performance and also to keep track on the shopping carts in KL Procurement Service Center one of the department in Schlumberger. This report also describes how the dashboards will support decision making in KL PSC day-to-day operations and how they will use the dashboards. This project is to improvise my Student Industrial Project in Schlumberger as my Final Year Project. It is to monitor the KL Procurement Service Center production in terms of checking the buyers’ performance and to check on the incoming and outgoing shopping carts in KL PSC. There are several efforts being done to reduce manual work to avoid human errors in KL PSC.